Modal Sosial Masyarakat KONI: Kajian Pelaksanaan Pasal 40 Undang-Undang No. 3 Tahun 2005 Sistem Keolahragaan Nasional Jawa Tengah - Rustiadi, Tri (Media Ilmu Keolahragaan Indonesia, 2013)
This study focused on the analysis of social capital of Indonesian National Sports Committee (KONI) which is potential to support the implementation of article40 Law No. 3/2005 about the National Sports System through networks and partnerships developed by KONI. By using qualitative method, this study took setting of KONI of Regency/City level in Central Java. To answer  the research questions, we analyzed the factual action done by KONI’s board by using emic analysis and ethic interpretation procedures. The result was analyzed based on the board relation with the structural/public figures, the developed networks, leadership, and achievement which has been accomplished. The conclusions are: (1) The social networks developed by KONI have not been maximized, for instance, KONI has not involved NGOs to fund the sports development; (2) The social capital of KONI including trust, social network, and authority structure have not been maximized, while the shared norms and shared values have been developed well